PERAN BIMBINGAN KONSELING DALAM MENINGKATKAN RESILIENSI SISWA YANG MENGHADAPI TANTANGAN AKADEMIK PADA SMP KARTINI 2 BATAM - Abdul Kodir (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Counseling guidance plays a crucial role in helping students overcome academic challenges and enhance resilience, particularly in junior high school settings. This study aims to analyze the role of school counselors in fostering student resilience amidst academic pressures at SMP Kartini 2 Batam. The research employs a qualitative approach using a case study method, with in-depth interviews, participatory observation, and document analysis as data collection techniques. The findings reveal that school counselors contribute through individual counseling, group counseling, and resilience training, effectively improving students' stress management, self-motivation, and problem-solving skills. However, the implementation of counseling programs faces challenges such as limited time, insufficient understanding among students and parents about the importance of counseling, and a lack of counselors, necessitating further strategies to optimize services.